2003
DOI: 10.1128/jb.185.1.254-261.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of the Phosphorylation Domain in PhoP Reveals a Functional Tandem Association Mediated by an Asymmetric Interface

Abstract: PhoP from Bacillus subtilis belongs to the OmpR subfamily of response regulators. It regulates the transcription of several operons and participates in a signal transduction network that controls adaptation of the bacteria to phosphate deficiency. The receiver domains of two members of this subfamily, PhoB from Escherichia coli and DrrD from Thermotoga maritima, have been structurally characterized. These modules have similar overall folds but display remarkable differences in the conformation of the ␤4-␣4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 52 publications
(58 reference statements)
3
39
0
Order By: Relevance
“…This would leave the α4-β5-α5 face of the regulatory domain available for formation of an active symmetric dimer and the effector domain free to bind DNA with a different symmetry. Additionally, the formation of the α4-β5-α5 dimer interface juxtaposes the linkers of the RRs on the same plane, as opposed to the dimers formed in inactive E. coli PhoB 64 and B. subtilis PhoP, 50 facilitating association of the effector domains into dimers for DNA binding. While this model is compatible with tandem binding to direct repeats, it does not exclude the possibility of other binding modes such as symmetric binding to inverted repeats as has been postulated for some OmpR/PhoB subfamily members.…”
Section: A Common Mechanism Of Regulation By Dimerizationmentioning
confidence: 99%
See 2 more Smart Citations
“…This would leave the α4-β5-α5 face of the regulatory domain available for formation of an active symmetric dimer and the effector domain free to bind DNA with a different symmetry. Additionally, the formation of the α4-β5-α5 dimer interface juxtaposes the linkers of the RRs on the same plane, as opposed to the dimers formed in inactive E. coli PhoB 64 and B. subtilis PhoP, 50 facilitating association of the effector domains into dimers for DNA binding. While this model is compatible with tandem binding to direct repeats, it does not exclude the possibility of other binding modes such as symmetric binding to inverted repeats as has been postulated for some OmpR/PhoB subfamily members.…”
Section: A Common Mechanism Of Regulation By Dimerizationmentioning
confidence: 99%
“…A multiple sequence alignment of the regulatory domains of all members of this subfamily from E. coli, 20 in addition to subfamily members from other organisms for which structures of the regulatory domain are available, 33,34,49,50 revealed that the residues involved in key dimer interface interactions are highly conserved within this subfamily (Fig. 5).…”
Section: Dimer Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the only available DNA complex structure is the DNA-binding domain of PhoB from E. coli in complex with its pho box DNA (16), which shows a tandem dimer. The N-terminal domain of PhoP from B. subtilis also has a tandem association in the crystal structure (8). However, crystal structures of the N-terminal domain of E. coli ArcA, TorR, and KdpE show that they form a symmetric dimer mediated by the α4-β5-α5 face (17,18).…”
mentioning
confidence: 99%
“…The phosphoryl group is then transferred to a conserved aspartate residue of PhoP (7), a response regulator that regulates the expression of particular genes (5). In Bacillus subtilis, the PhoP-PhoR system senses phosphate, being activated under limited phosphate conditions, and it regulates the expression of 31 genes that are involved in phosphate utilization (8). The related PhoP-PhoQ system in Salmonella enterica typhimurium, however, senses Mg 2+ (9), low pH (10,11), and antibacterial peptides (12,13); it regulates genes involved in Mg 2+ transport and acquisition and also controls the expression of several virulence factors (14).…”
mentioning
confidence: 99%